Cardiac Findings in COVID-19 Patients Treated with HAZDPac - Hazan, Sabine; Vidal, Adriana; Hulscher, Nicolas; Goudzwaard, Amelia; McCullough, Peter A; Steinberg, Alon (International Journal of Innovative Research in Medical Science, 2025)
Objective: Hydroxychloroquine paired with Azithromycin, Vitamin C, Vitamin D, and Zinc (HAZDPac), was used as a multidrug therapy method to treat COVID-19 illness and superimposed secondary bacterial pneumonia. Concerns have been raised though about such combinations regarding cardiac QTc interval prolongation and risks of arrhythmias, which we set out to address in this study. Design: We evaluated cardiac safety in a Phase II Double-Blind Randomized Placebo-Controlled Trial of Combination Therapy to Treat COVID-19 Infections study, conducted by ProgenaBiome. Acutely ill patients with COVID-19 had QTc intervals recorded in an outpatient setting utilizing a continuously worn EKG monitor for the duration of the 10 days treatment. QTc intervals were normally distributed. Two-sample t-tests were used to measure any significant differences in QTc intervals between treatment and placebo groups. Results: Between June 2020 and June 2021, 118 COVID-19 patients were recruited and signed informed consent, of which 83 were enrolled for a Double-Blind Randomized Placebo-Controlled Trial. Of the 83, 52 patients were randomly assigned to receive HAZDPac treatment, and 31 patients to receive placebo. Overall, and in stratified analysis by gender, maximum QTc values of patients in the treatment arm were normal and no differences were observed when compared to maximum QTc values from patients in the placebo arm (p≥0.15). There were no adverse events related to HAZDPac treatment. Conclusion: We found that the outpatient treatment of COVID-19 patients with HAZDPac which includes Hydroxychloroquine and Azithromycin, was not associated with prolongation of QTc compared to placebo and QTc remained within normal range.